2013
DOI: 10.1016/j.ccr.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2-Expressing Myeloid-Derived Suppressor Cells Are Essential to Promote Colitis-Associated Tumorigenesis

Abstract: Summary A large body of evidence indicates that chronic inflammation is one of key risk factors for cancer initiation, progression, and metastasis. However, the underlying mechanisms responsible for the contribution of inflammation and inflammatory mediators to cancer remain elusive. Here we present genetic evidence showing that loss of CXCR2 dramatically suppresses colonic chronic inflammation and colitis-associated tumorigenesis through inhibiting infiltration of myeloid-derived suppressor cells (MDSCs) into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
389
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(419 citation statements)
references
References 60 publications
(70 reference statements)
28
389
0
2
Order By: Relevance
“…20-22 It has been well recognized, in studies of both pre-clinical and clinical samples, that MDSCs are enriched in the tumor infiltrated tissue in solid tumors. 23,24 In addition, significant expansion of MDSCs in peripheral blood has been reported in patients with multiple myeloma, non-Hodgkin’s lymphoma and chronic lymphocytic leukemia. 25-27 However studies on the contributions of MDSCs to the pathogenesis of AML are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…20-22 It has been well recognized, in studies of both pre-clinical and clinical samples, that MDSCs are enriched in the tumor infiltrated tissue in solid tumors. 23,24 In addition, significant expansion of MDSCs in peripheral blood has been reported in patients with multiple myeloma, non-Hodgkin’s lymphoma and chronic lymphocytic leukemia. 25-27 However studies on the contributions of MDSCs to the pathogenesis of AML are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IL‐6, IL‐8, and IL‐1β, another ZEB1‐regulated cytokine, G‐CSF/CSF3, also enhances the accumulation of MDSCs (Talmadge and Gabrilovich, 2013). ZEB1 also regulates the expression of the chemokines CXCL1 and CXCL5, which are the ligands for the CXCR2 receptor, and increases the infiltration of PMN‐MDSCs (Acharyya et al ., 2012; Katoh et al ., 2013; Toh et al ., 2011). Although the present study showed no additional effect of ZEB1 on tumor progression or on the metastasis of 4T1 cells, which may be due to the aggressive nature of the parental 4T1 cells, these observations suggest that inflammatory cytokines induced by ZEB1 play critical roles in the progression of cancer in a context‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays an essential role in initiating tumorigenesis by damaging specific tissues 100 (Figure 3). In these models, neutrophils are attracted to tumor-prone tissues via the CXCR2 ligands, CXCL1, CXCL2 and CXCL5 [101][102][103][104] . Application of these carcinogens to CXCR2-deficient mice, which show impaired neutrophil trafficking, prevents papilloma or adenoma formation 102,104 .…”
Section: Neutrophils and Tumor Initiationmentioning
confidence: 99%
“…In these models, neutrophils are attracted to tumor-prone tissues via the CXCR2 ligands, CXCL1, CXCL2 and CXCL5 [101][102][103][104] . Application of these carcinogens to CXCR2-deficient mice, which show impaired neutrophil trafficking, prevents papilloma or adenoma formation 102,104 . Similarly, CXCR2 ligands are increased in several genetically engineered mouse models, including the intestinal adenoma Apc Min/+ model, the invasive intestinal adenocarcinoma Ah-CreER;Apc F/+ ;Pten F/F model and the spontaneous oral papilloma K14-CreER;Kras G12D/+ model.…”
Section: Neutrophils and Tumor Initiationmentioning
confidence: 99%